Gênese da educação profissional feminina no Ceará: o colégio de economia doméstica rural no município de Iguatu (1955-1983) - Lima, Maria Luciene Ferreira (2023)
This research aimed to provide a historical retrospective of the College of Rural Home Economics of Iguatu Ceará (Colégio de Economia Doméstica Rural de Iguatu Ceará), focusing on management Elze Alves Lima Verde Montenegro, the first supervisor that gave rise to the institution. Founded in 1955, the institution began its activities focused on female professional education. The study is situated in the field of History of Education, especially the history of school institutions and agricultural education, anchored in the pertinent contribution of historiographic studies of Cultural History and Political History, based on the use of memory. We seek, therefore, to reconstruct a memory based on the social praxis of a subject based on authors such as Bourdieu (2002, 2004, 2008) and Sirinelli (2003). We work with the concepts of memory, representation and appropriation, agricultural education, professional education, integral education and the categories of gender, rural and urban. To analyze the sources, we used the historiographical aspect of the Indicial Paradigm (Ginzburg, 1989; 2008), a theoretical contribution used to help fill in some gaps left by the memories expressed in our archives. Within our time frame, the researched school goes through four phases: 1) (1955-1963) - Implementation - First Extension courses in Home Economics, governed by the guidelines of the Capanema Reform and administered by the Ministry of Agriculture; 2) (1963-1967) - Construction of its own headquarters and start of operation of the Technical Courses in Home Economics, an offshoot of the LDB of 1961; 3) (1967-1971) – Agricultural schools are transferred to the Ministry of Education; 4) (1971-1983) – The “Elza Barreto” Rural Home Economics College remains federalized and becomes the Federal Agrotechnical School. The thesis we intend to defend is that the Extension Courses in Domestic Rural Economics, installed at the time, were designed not only to prepare girls for family management, but also as an alternative to comprehensive education for the training of human resources capable to act in defense of territorial interests. It was not enough to just teach how to read, write and count, it was necessary to invest in the moral and civic training of the subjects, so that they felt an important part of their locality and co-responsible for the economic, social and cultural development of their community and, thus, avoid the rural exodus. Education was the social resource used to prepare people capable of using their knowledge and technologies to serve their locality and/or region.